jurnal metode penelitian: Negara Hukum Dan Penegak Hukum Di Indonesia - manda sari (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
The Indonesian nation since the 1945 Constitution was established as the Constitution of the Indonesian state. In its development, this agreement has transformed into a common ideal which is also usually called state philosophy or staatsidee (state ideals). In the concept of democracy, it contains the principles of popular sovereignty (democratie) while in the concept of the rule of law, it contains the principles of the rule of law (nomocratie). Law enforcement mechanisms must also be able to protect the rights of citizens from injustice with the principles of humanity and mutual respect for the continuity of existing laws. This becomes an integral part of the legal system with law enforcement authorities. Indonesia as a democratic rule of law country, adheres to the sovereignty of the people as well as the rule of law.search for research titles and abstracts is made easier by those key words.